GABAergic anxiolytic drug in water increases migration behaviour in salmon - Gustav Hellström (Nature Portfolio, 2016)
Fish migration is influenced by various environmental factors such as chemicals in water. Here, Hellstrom et al. show that an anxiolytic drug in the benzodiazepine family, oxazepam, can promote migratory behaviour of Atlantic salmon smolts in both laboratory setting and river tributary in Sweden.